MIRTAZAPINE PHARMACOKINETICS IN HEALTHY THAI VOLUNTEERS: Pharmaceutical Science-Toxicology - PONGTANYA, SURACHET; SANICHWANKUL, KITTIPONG; WANMANEE, SOMKUAN; SOMBOON, BUSAKORN; PUMPAISALCHAI, WANIDA (International Journal of Life Science and Pharma Research, 2012)
Mirtazapine (MZP) is a third-generation antidepressant with a dual mode of action. To investigate the pharmacokinetic profile of MZP in 22 healthy Thai volunteers (12 males, 10 females), each volunteer received a single 30mg oral dose of MZP in the form of conventional tablets, in the fasting state. Serial blood samples were taken and MZP plasma concentrations were measured from 0 to 72 h by a HPLC-UV spectrometry validated method. Pharmacokinetic parameters were calculated and statistically analyzed from MZP plasma levels. Means ± standard deviations of the pharmacokinetic parameters were as follows: The rate of absorption, as measured by peak level (Cmax) and peak time (tmax) were 169.9 ± 31.5 ng ml−1 and 0.6 ± 0.2 h, respectively. The extent of absorption, as measured by area under the curve from zero time to the last measurable sampling time (AUC0-last), and total area under the curve from time zero to infinity (AUC0-inf), were 564.4 ± 241.6 ng ml−1 h and 678.6 ± 283.9 ng ml−1 h, respectively. Elimination rate, characterized by termination half-life (t1/2), was 10.4 ± 5.6 h. A comparison with published pharmacokinetic studies on MZP demonstrated a significantly greater absorption rate and elimination in Thai subjects. Meanwhile, the total extent of absorption (AUC0-inf ) of MZP was not different (p>0.05).